Advanced Multiple Access Schemes for Multimedia Traffic over Wireless Channels - Habaebi, Mohamed Hadi (2001)
To meet the anticipated demand for wireless access to the broadband Asynchronous Transfer Mode (ATM) network, the concept of wireless ATM has been proposed in 1994 [1]. One of the main challenges in the design of a wireless ATM network resides in the conception of a Medium Access Control (MAC) protocol that will handle the different ATM services while providing an efficient utilization of the wireless channel. In this thesis, we propose a new Adaptive Reservation TDMA (AR-TDMA) MAC protocol for wireless ATM networks. AR-TDMA combines the advantage of distributed access and centralized control for transporting Constant Bit Rate (CBR), Variable Bit Rate (VBR) and Available Bit Rate (ABR) traffic efficiently over a wireless channel. The contention slots's access is governed by two novel framed pseudo-Bayesian priority Aloha protocols that we introduce in this thesis. Either one of these protocols can minimize the contention delay and provide different access priorities for heterogeneous traffic. Analytical and simulation results indicate that the framed pseudo-Bayesian priority Aloha protocols offer a significant delay improvement for high priority packets with Poisson traffic, while low priority packets only experience a slight performance degradation. A detailed comparison and discussion of implementation and robustness issues is presented in this thesis to help the design engineer choose the right protocol that suits the application scenario. In the context of the AR-TDMA protocol, results show that the priority algorithms improve real-time traffic Quality-of-Service (QoS). The AR-TDMA resource allocation algorithm grants to terminals reserved access to the wireless ATM channel by considering their requested bandwidth and QoS. We propose scheduling algorithms for CBR, VBR and ABR traffic. Furthermore, we also introduce a method to dynamically adjust the number of uplink control slots per frame as a function of the estimated contention traffic. Finally, an algorithm is proposed to integrate these algorithms to provide ubiquitous wireless ATM services. Performance results show that the AR-TDMA MAC protocol can achieve high throughput in the range of 90 to 95% while maintaining reasonable QoS for all ATM services.